Numerical modeling of cavitating flows for simple geometries using FLUENTV6.1 - Palau Salvador, G.=700 1 Gonzalez Altozano, P.; Arviza Valverde, J.
(Es, En)
Ilus., 15 ref.
Keywords: CONEJO (ORYCTOLAGUS); AMINOACIDOS; CONSUMO DE PIENSO; DIGESTIBILIDAD; GANANCIA DE PESO; ESPAÑA; GAZAPOS